The Effort To Increase Production of Super Red Dragon Fruit (Hylocereus costaricensis) By Artificial Pollination - Neni Andayani; Lailatun Naria Latifah; Theresia Maria Astuti (UNEJ e-Proceeding, 2016)
This study aims to increase production of super red dragon fruit (Hylocereus costaricensis) by artificial pollination. The study was conducted from January to April 2016 at dragon fruit plantation located in Sleman, Yogyakarta, Indonesia. The research was done on two groups of artificial pollination. Those were P0, P1 and P2. P1 was a group of the pollen derived from white dragon fruit (Hylocereus Undatus), P2 was a group of the pollen derived from red dragon fruit (Hylocereus polyrhizus), and P0 was a group of super red dragon fruit natural pollination as control. Artificial pollination of fruit set was done by tapping pollen on the stigma of super red dragon fruit flowers receptive. The results showed that artificial pollination with white dragon fruit pollen or red dragon fruit pollen can increase the weight of super red dragon fruit production 11% larger than the weight of super red dragon fruit production on natural pollination.